Historical fish catch in the Huave Lagoon System, Oaxaca, Mexico - Cervantes-Hernández, Pedro; Alejo-Plata, María del Carmen; López-Serrano, Antonio; Gallardo-Berumen, María Isabel (Revista Ciencias Marinas y Costeras, 2014)
In the Huave Lagoon System (HLS), the Huave area is comprised of four lagoon bodies: the Mar Tileme Lagoon and adjacent areas, the Inferior Lagoon and the Oriental - Occidental Lagoons. Based on monthly records of fish catches (Kg) and fishing effort (days of fishing), the “fishing pressure” index was estimated from 1999 to 2007 in order to evaluate the potential availability (PA) and exploitation level (EL) for this resource. In the Mar Tileme Lagoon and adjacent areas, the “fishing pressure” was low. In the Inferior Lagoon, the “fishing pressure” was high, while in the Oriental - Occidental Lagoons it showed intermediate magnitudes. Results were compared with HLS documented hydrology from May to August / October 2007, evidencing that where hydrology was persistently extreme (44 - 54.7 PSU, 29.2 - 30°C, 5.0 - 6.7 mg/l Dissolved Oxygen (DO)), PA and EL were lower (in the Mar Tileme Lagoon and adjacent areas), and where hydrology was persistently intermediate (22.5 - 30.0 PSU, 27.0 - 28.1ºC, 7.6 - 8.0 mg/l DO), PA and EL were higher (in the Inferior Lagoon). Intermediate magnitudes for PA and EL were recorded where hydrology was persistently optimal (11.1- 22.5 PSU, 27.0 - 28.6ºC, 6.7 - 7.6 mg/l DO) (in the Oriental - Occidental Lagoons).